Synthesis of 4‐C‐β‐D‐Glucosylated Isoliquiritigenin and Analogues for Aldose Reductase Inhibition Studies. Issue 24 (24th June 2019) - Reddy, Mannem Rajeswara; Aidhen, Indrapal Singh; Reddy, Utkarsh A.; Reddy, Geereddy Bhanuprakash; Ingle, Kundane; Mukhopadhyay, Sami
Abstract : Inspired from natural product isoliquiritine, an O ‐glucoside and the corresponding aglycon chalcone, isoliquiritigenin (ISL), several C ‐glucosylated chalcones and dihydrochalcones have been synthesized and evaluated for aldose reductase (AR) inhibition activity, for the first time. The initial inputs from molecular docking studies were also encouraging. Claisen‐Schmidt condensation reaction between 4‐ C ‐glucosylated benzaldehyde, a key building block developed during the synthetic efforts and acetophenones enabled convenient access to the targeted compounds in good yields. Excellent AR inhibition has been observed with C ‐glucosylated ISL with IC50 value of 21 µM. This is similar to the chalcone ISL, displaying IC50 of 19 µM. In the light of limited aqueous solubility of ISL, the observed AR inhibition with C ‐glucosylated ISL, gains importance. Additionally, the studies have revealed significance of the oxygenation pattern on the aromatic residue and paved way for the identification of few more new compounds with equally promising AR inhibition. Abstract : Inspired from natural product isoliquiritigenin (ISL), to enhance the bioavailability of ISL, 4‐ C ‐glucosylated isoliquiritigenin and several C ‐glucosylated chalcones have been synthesized and evaluated for aldose reductase (AR) inhibition activity. Excellent AR inhibition has been observed with C ‐glucosylated ISL with IC50 value of 21 µM which is similar to the chalcone ISL (IC50 of 19 µM). The studies have revealed few new analogues with promising activity.